(untitled) - Bronson, Richard (New York, 1994)
If you want top grades and thorough understanding of differential equations, this powerful study tool is the best tutor you can have! It takes you step-by-step through the subject and gives you 563 accompanying problems with fully worked solutions. You also get plenty of practice problems to do on your own, working at your own speed. (Answers at the back show you how you're doing.) Famous for their clarity, wealth of illustrations and examples, and lack of dreary minutiae, Schaum's Outlines have sold more than 30 million copies worldwide--and this guide will show you why!
Keywords: Differential equations,Phương trình vi phân